MORPHOLOGICAL AND PHYSIOLOGICAL CHANGES OF GROUNDNUT PLANTS BY FOLIAR APPLICATION WITH SALICYLIC ACID - G. Renuka AND S.madhu (The Bioscan, 2022)
The purpose of this research is to examine the effects of salicylic acid applied topically to groundnut plants at concentrations of 100, 200, and 400 mg/L on the plant's vegetative development, photosynthetic pigment content, yield, and several biochemical components of groundnut grains, as well as the interactions between these factors. There was a positive correlation between plant growth characteristics and yield, according to the data. After adding 100 or 200 mg/L of salicylic acid (SA), groundnut grains exhibited an increase in total carbohydrates, lipids, and proteins. Results for yield and the aforementioned components were lowest when SA was administered at 400 mg/L in comparison to the control groups.